UPAYA GURU DALAM MENINGKATKAN HASIL BELAJAR MELALUI METODE DEMONSTRASI PADA MATA PELAJARAN PENDIDIKAN JASMANI OLAHRAGA DAN KESEHATAN (PJOK) DI KELAS II MIN 1 TAPANULI SELATAN - sahnul habibi harahap; Nursyaidah (Jurnal Binagogik, 2026)
This study was motivated by the low student learning outcomes in Physical Education, Sports, and Health (PJOK) classes for Grade II students at MIN 1 South Tapanuli. Many students paid little attention to the teacher during lessons because the teaching methods employed lacked variety, resulting in low student engagement. The study aimed to determine student learning outcomes when using the demonstration method in PJOK classes at MIN 1 South Tapanuli. This was a classroom action research study comprising an initial baseline phase, Cycle I, and Cycle II, with each cycle consisting of two meetings. The subjects were 19 Grade II students. Data collection instruments included observation sheets and tests. Improvements were assessed based on test results and observations conducted by the researcher. During the pre-cycle phase, the average score for Grade II students was 54.2, with a mastery rate of 12.7%. In Cycle I, the average score was 63.1 with a mastery rate of 31.5% at the first meeting, and 70.0 with a mastery rate of 47.4% at the second meeting. In Cycle II, the average score was 74.7 with a mastery rate of 63.1% at the first meeting, and 79.4 with a mastery rate of 84.2% at the second meeting. The results across these cycles demonstrate an increase in average scores and mastery rates, indicating that the use of the demonstration method (supported by audiovisual media) can improve student learning outcomes in Physical Education, Sports, and Health.